The predacious Coccinellidae associated with the wheat aphid, Schizaphis graminum (Rond.) in the Orange Free State - Brown, Hubert Dick (Stellenbosch : Stellenbosch University, 2012)
Thesis (DSc) -- University of Stellenbosch, 1969.